The dichotomous outcomes of TNFα signaling in CD4+ T cells - Skartsis, Nikolaos; Ferreira, Leonardo M. R.; Tang, Qizhi (Frontiers in Immunology, 2022)
TNFa blocking agents were the first-in-class biologic drugs used for the treatment of autoimmune disease. Paradoxically, however, exacerbation of autoimmunity was observed in some patients. TNFa is a pleiotropic cytokine that has both proinflammatory and regulatory effects on CD4+ T cells and can influence the adaptive immune response against autoantigens. Here, we critically appraise the literature and discuss the intricacies of TNFa signaling that may explain the controversial findings of previous studies. The pleiotropism of TNFa is based in part on the existence of two biologically active forms of TNFa, soluble and membrane-bound, with different affinities for two distinct TNF receptors, TNFR1 and TNFR2, leading to activation of diverse downstream molecular pathways involved in cell fate decisions and immune function. Distinct membrane expression patterns of TNF receptors by CD4+ T cell subsets and their preferential binding of distinct forms of TNFα produced by a diverse pool of cellular sources during different stages of an immune response are important determinants of the differential outcomes of TNFa-TNF receptor signaling. Targeted manipulation of TNFa-TNF receptor signaling on select CD4+ T cell subsets may offer specific therapeutic interventions to dampen inflammation while fortifying immune regulation for the treatment of autoimmune diseases.